Chemical Constituents from the Flowers of Wild Gardenia jasminoides J.Ellis. Issue 5 (5th April 2017) - Zhang, Hu; Feng, Ning; Xu, Yan‐Tong; Li, Tian‐Xiang; Gao, Xiu‐Mei; Zhu, Yan; Song, Yun Seon; Wang, Ya‐Nan; Wu, Hong‐Hua
Abstract : Four new iridoids, 2′‐ O ‐( E ) ‐ coumaroylshanzhiside (1 ), 6′‐ O ‐( E ) ‐ coumaroylshanzhiside (2 ), 8 α‐ butylgardenoside B (3 ), 6 α‐ methoxygenipin (4 ), and one new phenylpropanoid glucoside, 5‐(3‐hydroxypropyl)‐2‐methoxyphenyl β ‐d ‐glucopyranoside (5 ), together with sixteen known compounds, were isolated from the edible flowers of wild Gardenia jasminoides J.Ellis . Their chemical structures were characterized by extensive spectroscopic techniques, including 1D‐ and 2D‐NMR, HR‐ESI‐MS, and CD experiments. The absolute configurations of the new isolates' sugar moiety were assigned by HPLC analysis of the acid hydrolysates. Furthermore, the antioxidant activities of those isolates were preliminarily evaluated by DPPH scavenging experiment. And comparison of 1 H‐NMR spectra for the EtOH extract of G .  jasminoides J.Ellis, gardenoside B and geniposide revealed that the flowers of this plant have a considerable content of gardenoside B instead of geniposide in the fruits, indicating different activities and applications in people's daily life. Abstract :